Manual de marca de “Sunmoon”, empresa de servicios de brand experience - Garmendia Mohanna, Alejandra Claudia (2023)
This work consists of the creation of the brand manual that manages to transmit the brand's value proposition and generate a powerful and attractive identity of "Sunmoon", a consultancy dedicated to the development of comprehensive communication strategies that seek to improve the consumer's shopping experience. final, especially for companies and brands in the gastronomic sector in the Peruvian market. For the creation of the brand manual, which includes information about the brand, variants, visual style and applications as part of a brandbook, an investigation was carried out on the business and competition of the company. In addition, it is complemented with corporate tools such as: the website and the menu of services. These must generate trust, so a review of each one is made. Finally, the validations throughout the process are mentioned as well as the lessons learned from carrying out the work.